The Role of Biochar and Combination of Inorganic Fertilizers and Biological Fertilizers in Increasing Yield and Levels of Brix Sorghum (Sorghum bicolor (L.) Moench) in Dry Land - Husni Idris; Hadromy Hawari; Suwardji Suwardji (Postgraduate, University of Mataram, 2021)
Research on the role of biochar, inorganic and biological fertilizers was aimed to increase crop yield and brix value of sorghum in dryland. This research was conducted from October 2020 to February 2021 at The Teaching Farm Soil Science Study Program, Akar-Akar Village, Bayan, North Lombok. The method used in this research is an experimental method, with the experimental plot in the field. The experiment consisted of two factors, was designed using a split plot design. Biochar as the main plot with 2 treatment levels, b0 (without biochar) dan b1 (biochar 20 ton/ha); combination of fertilization as subplots with 4 treatment levels, namely p0 (without fertilizer), p1 (200 kg/ha NPK + 150 kg/ha Agrosil), p2 (20 ml/liter PGPR), and p3 (200 kg/ha NPK + 150 kg/ha Agrosil + 20 ml/LÂ PGPR). The research showed that interaction between biochar and combination of fertilizers is not significant, but the combination of inorganic and biological fertilizers significantly increased sorghum's productivity and brix value. The combination of inorganic and biological fertilizer (p3) is the best treatment to increase weights 1000 seeds (31.29 g), yield (25.96 kg/plot), and brix value (14.55%)